1996
DOI: 10.1038/nbt0596-635
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccumulation of nickel by intercalation into polycrystalline hydrogen uranyl phosphate deposited via an enzymatic mechanism

Abstract: A Citrobacter sp. accumulates uranyl ion (UO2(2+)) as crystalline HUO2PO4.4H2O (HUP), using enzymatically generated inorganic phosphate. Ni was not removed by this mechanism, but cells already loaded with HUP removed Ni2+ by intercalative ion-exchange, forming Ni(UO2PO4)2.7H2O, as concluded by x-ray diffraction (XRD) and proton induced x-ray emission (PIXE) analyses. The loaded biomass became saturated with Ni rapidly, with a molar ratio of Ni:U in the cellbound deposit of approx. 1:6; Ni penetration was proba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 28 publications
2
28
0
Order By: Relevance
“…Macaskie et al (1997) reported on the successful use of Class A NSAPs as tools for environmental bioremediation of uranium-bearing wastewater, and Baskanova and Macaskie (1997) and Bonthrone et al (1996) on heavy metal biomineralization (particularly Ni 2+ ). A new biotechnological application for NSAPs would be to transfer and express these genes in PGPB to obtain improved phosphatesolubilizing strains using recombinant DNA technology.…”
Section: Nonspecific Acid Phosphatasesmentioning
confidence: 99%
“…Macaskie et al (1997) reported on the successful use of Class A NSAPs as tools for environmental bioremediation of uranium-bearing wastewater, and Baskanova and Macaskie (1997) and Bonthrone et al (1996) on heavy metal biomineralization (particularly Ni 2+ ). A new biotechnological application for NSAPs would be to transfer and express these genes in PGPB to obtain improved phosphatesolubilizing strains using recombinant DNA technology.…”
Section: Nonspecific Acid Phosphatasesmentioning
confidence: 99%
“…3e) showing clearly the cell-surface localization of the uranyl phosphate, the identity of which was confirmed as H U 0 2 P 0 , . 4 H 2 0 using EDAX, PIXE and XRD, as reported previously (Macaskie et al, 1992;Yong & Macaskie, 1995;Bonthrone et al, 1996). The localization of H U 0 2 P 0 4 .…”
Section: Further Studies Of Uranyl Ion Uptake By Strains N14 and Dc5cmentioning
confidence: 99%
“…AFM was done using wet or briefly air-dried mounts in water on glass slides in the laboratories of the Company Research Laboratory, BNFL, Preston, UK. The accumulated solid material was characterized using EDAX and PIXE as described previously (Bonthrone et al, 1996;Tolley et al, 1995 ;Yong & Macaskie, 1995), and the identity of the deposit was confirmed by XRD (Bonthrone et al, 1996;Yong & Macaskie, 1995) and comparison with appropriate reference databases (Bonthrone et al, 1996).…”
Section: Fixation and Embedding Of Cells For Electron Microscopymentioning
confidence: 99%
“…via biogenic phosphate release can be used as the 'priming' deposit for subsequent deposition of actinide phosphates (Macaskie et al 1994). Also, by use of a priming deposit with an appropriate, well-defined cystalline lattice, the target metal can be intercalated within the 'host' lattice, effectively by a mechanism of bioinorganic ion-exchange, well-established as a chemical process (Clearfield 1988;Pham-Thi & Columban 1985;Pozas-Tormo et al 1987) and best-characterized biologically in the case of Ni 2+ removal into biomass-bound HUO 2 PO 4 AEnH 2 O (Bonthrone et al 1996). Within the context of nuclear waste remediation, the approach of MECHM, using biogenic hydrogen uranyl phosphate as the 'host' matrix, and using either intercalative ion exchange or co-crystallisation, has been applied to the removal of Cs, Co and Sr from 'surrogate' solutions and the isotopes 137 Cs, 60 Co and 90 Sr from real nuclear wastes in South Korea (Paterson-Beedle et al unpublished).…”
Section: Microbially Enhanced Chemisorption Of Heavy Metalsmentioning
confidence: 99%